Solid Silicon Microneedles for Safe and Effective Drug Delivery to Human Eye - Abser, Md Nurul (Journal of Electrical Engineering, 2011)
Guidelines on the fabrication of solid, out-of-plane Silicon (Si) microneedles for drug delivery to the posterior segment of human eye have been provided. The posterior and the anterior chambers of the human eye have been studied along with the major obstacles to drug delivery, and thereafter a minimally invasive route for systematic drug delivery to the back segment was selected. Microneedle parameters were chosen so that drugs can be delivered successfully through the selected route. The entire fabrication process was simulated and the resultant micro structures have been reported and analyzed. A mechanical strength analysis was subsequently carried out for solid out-of-plane Si microneedles by using column buckling and bending forces. The data obtained from the analysis indicated that the fabricated needles should be able to withstand the pressure exerted by a thin layer of fibrous human tissue. Index Terms: Microneedle; posterior eye segment; ocular delivery; RIE; etch isotropy; tissue resistance; scleral route; cornea; ocular barrier. J. Elec. Engg., Instn. Engrs., Bangladesh, 36(II), December 2009: 28-34